2013
DOI: 10.1016/j.micres.2013.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum passage through an oro-gastro-intestinal tract simulator: Carrier matrix effect and transcriptional analysis of genes associated to stress and probiosis

Abstract: Dietary probiotics should reach the intestine viable and in high numbers; therefore, they should tolerate the stress associated to the gastro-intestinal (GI) environment. Indeed, all along the different GI sections, probiotics are challenged by several sources of stress, including low pH, bile and digestive enzymes. Bacterial cells are equipped with various defense mechanisms to allow survival in hostile environments. The food matrix used to deliver beneficial bacteria may contribute to their probiotic action,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 81 publications
5
56
1
Order By: Relevance
“…1). Other researchers have also observed high rates of probiotic inactivation at gastric pH levels (Bove et al, 2013.;Mainville, Arcand, & Farnworth, 2005;Marteau, Minekus, Havenaar, & Huis In't Veld, 1997). Ranadheera et al (2012) reported that during a simulated gastrointestinal study, a greater probiotic bacterial inactivation occurred when the pH was 2 compared to pH at 3 or 4.…”
Section: Fig 1 Shows Cell Population Reductions In Samples Inoculatedmentioning
confidence: 95%
See 1 more Smart Citation
“…1). Other researchers have also observed high rates of probiotic inactivation at gastric pH levels (Bove et al, 2013.;Mainville, Arcand, & Farnworth, 2005;Marteau, Minekus, Havenaar, & Huis In't Veld, 1997). Ranadheera et al (2012) reported that during a simulated gastrointestinal study, a greater probiotic bacterial inactivation occurred when the pH was 2 compared to pH at 3 or 4.…”
Section: Fig 1 Shows Cell Population Reductions In Samples Inoculatedmentioning
confidence: 95%
“…Ranadheera et al (2012) reported that during a simulated gastrointestinal study, a greater probiotic bacterial inactivation occurred when the pH was 2 compared to pH at 3 or 4. Bove et al (2013) studied the effect of a food matrix on the survival of L. plantarum through an oro-gastro-intestinal tract simulator. A lower probiotic survival occurred when the pH of the food matrix was 1.5 as compared to probiotic survival rate at higher pH levels.…”
Section: Fig 1 Shows Cell Population Reductions In Samples Inoculatedmentioning
confidence: 99%
“…These bacteria have been suggested to contribute to nutrient digestion, development, and maintenance of appropriate mucosal immune functions. Furthermore, some microorganisms provide essential vitamins (e.g., folate, biotin, vitamin K) and produce short-chain fatty acids that are used as energy source by colon cells (Gerritsen et al 2011;Bove et al 2013;Arena et al 2014)). …”
Section: Exopolysaccharides-host Interactionsmentioning
confidence: 99%
“…Despite the survival of probiotics is genus-, species-, and strain-dependent, the composition of the food matrix may also affect the bacterial viability (Del Piano et al, 2006). In this respect, it has been reported that food matrixes commonly used to deliver the bacteria can effectively protect them from hostile environments (Bove et al, 2013). In contrast, some food ingredients (e.g., sugars, vitamins) or additives frequently employed during the preparation of commercial foods such as synthetic antioxidants (such as TBHQ, BHT, BHA), iodized salt, and flavor enhancers (e.g.…”
Section: Discussionmentioning
confidence: 99%